2021 update of the AGIHO guideline on evidence-based management of COVID-19 in patients with cancer regarding diagnostics, viral shedding, vaccination and therapy. (April 2021) - Giesen, Nicola; Sprute, Rosanne; Rüthrich, Maria; Khodamoradi, Yascha; Mellinghoff, Sibylle C.; Beutel, Gernot; Lueck, Catherina; Koldehoff, Michael; Hentrich, Marcus; Sandherr, Michael; von Bergwelt-Baildon, Michael; Wolf, Hans-Heinrich; et al.
Abstract: The worldwide spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the associated infectious coronavirus disease (COVID-19) has posed a unique challenge to medical staff, patients and their families. Patients with cancer, particularly those with haematologic malignancies, have been identified to be at high risk to develop severe COVID-19. Since publication of our previous guideline on evidence-based management of COVID-19 in patients with cancer, research efforts have continued and new relevant data has come to light, maybe most importantly in the field of vaccination studies. Therefore, an update of our guideline on several clinically important topics is warranted. Here, we provide a concise update of evidence-based recommendations for rapid diagnostics, viral shedding, vaccination and therapy of COVID-19 in patients with cancer. This guideline update was prepared by the Infectious Diseases Working Party (AGIHO) of the German Society for Haematology and Medical Oncology by critically reviewing the currently available data on these topics applying evidence-based medicine criteria. Highlights: Immunocompromised patients are at risk of prolonged viral shedding of SARS-CoV-2. Remdesivir still has a role in COVID-19 therapy in patients with cancer. Vaccination of patients with cancer against COVID-19 is recommended. Patients with cancer with active disease should be prioritised for vaccination.